The function of “plant biltong” collected by bush Karoo rats (Otomys unisulcatus) - Sanweni Siyabong Patrick (University of the Witwatersrand, Johannesburg, 2024)
Food storing is a commonly observed strategy in many rodents living in environments with seasonally fluctuating food availability. Stored food allows small mammals to survive through food restricted periods and has been extensively studied in the northern hemisphere, characterised by cold winters. It could also be adaptive in semi-deserts of the southern hemisphere, such as the Succulent Karoo, which experience winter rainfall and hot dry summers. Here I want to understand the function of food plants carried back by bush Karoo rats (Otomys unisulcatus) to the stick lodges they build in the Succulent Karoo. Some of the food plants carried back to their lodges dry out, forming what I refer to as “plant biltong” or ‘plantong.’ To date, the function of the plantong remains unknown. Plantong might function as food in the dry season, or it might just be left over from food eaten at the lodge, or it can aid in construction of the lodges. I studied which plant species were collected as plantong, and whether there were seasonal differences in collection and consumption of plantong. I observed 15 lodges over 12 months and recorded the fate of plant pieces carried back to each lodge by bush Karoo rats. I tested experimentally whether they do eat the plantong. Plant species that were collected and dried out to become plantong were mostly annual shrubs (Zygophyllum retrofractum, Lycium cinereum, Salsola zeyheri, Helichrysum), grass species (Schismus) and perennials species (Atriplex, Drosanthemum spec, Galenia sarcophylla, Hermannia, Mesembryanthemum, oxalis sp, Chlorophytum crassinerve, Psilocaulon sp.). Most plant pieces were collected in winter and spring which is in the moist season. Plantong was consumed the most in the autumn (end of the dry season). Collected plant pieces were multifunctional. Most, 68%, of plant pieces carried back to the lodge were eaten green before they became plantong,Of the plant pieces that were collected, 12% were later eaten as plantong, 11% was incorporated into the structure of the lodge, while the fate of 9% was unknown. Experiments in captivity showed that bush Karoo rats indeed eat plantong. Plantong was not stored for months (from moist to dry season), but mostly days to weeks. Thus, I regard plantong as a food source derived from leftover food during collection and consumption but not as stored food for later consumption during harsh conditions.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg in partial fulfillment of the requirements for the degree of Master of Science Johannesburg, 2024
Keywords: Function of “plant biltong”; Bush Karoo; Stored food; UCTD; SDG-15: Life on land